Water Resources and Geopolitical Tensions in the Himalayas: Analysing Nepal’s Mediating Role - Gajurel, Kiran Prasad (Medha: A Multidisciplinary Journal, 2024)
The Himalayan region, often regarded as the ’water tower’ of Asia, is crucial for sustaining millions of people across Asia. As climate change exacerbates water scarcity, competition over shared water resources has intensified geopolitical tensions between India and China, particularly concerning the Indus and Brahmaputra river basins. This research posits that the escalating competition over shared water resources in the Himalayan region, intensified by climate change and nationalistic narratives from India and China, necessitates an exploration of Nepal’s mediating role, cooperative frameworks from other regions, and sustainable practices to alleviate tensions and promote regional stability, ultimately informing policymakers on effective strategies for conflict resolution and governance amid growing geopolitical challenges. Furthermore, it examines Nepal’s diplomatic strategies aimed at balancing its relationships with both powers while asserting its own interests. By analysing successful frameworks for mediation and cooperation from other regions, such the Mekong River basin, this study proposes actionable strategies for enhancing collaborative water management among India, China, and Nepal. This article is based on both secondary information as well as primary data sources. Under primary sources, in-depth interview has been taken from the three selective experts. Such experts were selected purposively on the basis of their fields of expertise. Similarly, for the secondary information, previously published articles and journals of the scholars from the diverse background has been reviewed and critically analysed. Their views are compared and contrasted to come to the logical conclusion regarding this field. The findings of this research suggest that the regional disputes in the twenty first century is an established fact, and one of the reasons of this tension is, of course, not other than the water resources and geopolitical strategies. Fostering sustainable practices and establishing transparent data-sharing mechanisms can alleviate such tensions and promote regional stability between and among the countries. Ultimately, this research emphasizes the importance of cooperative frameworks in addressing the challenges posed by water resource competition in the Himalayas and calls for further exploration of Nepal’s role in facilitating peace and conflict management in the region. This study contributes to the understanding of the intersection between water resources and geopolitics, providing insights that are critical for policymakers and stakeholders invested in the sustainable management of shared water resources in the Himalayas.